Usaha Perikanan Darat di Kabupaten Pangkajene 1989-1998 - Mansyur, Khumairah; Ahmadin, Ahmadin; Ridha, Rasyid (Universitas Negeri Makassar, 2021)
This research is focused on the impact of the existence of inland fisheries business in Pangkajene and Kepulauan Regency in 1989-1998. This research is a type of historical research that is qualitative in nature and is a type of case study based on a micro, commercial and social group theory approach to identify and interpret Land Fishing Enterprises in Pangkajene and Kepulauan Regency. Methodologically, the data source in this study uses the type of historical study sources in general, namely primary data obtained from observations and direct interviews with informants who are then supported by secondary data in the form of written references such as archives, journals, books and various media and documentation. Data analysis is descriptive, that is to describe in a systematic and factual way related to the phenomenon of research so that it can draw a conclusion. The existence of the Fisheries Business underwent several phases to be able to survive until now. some of the impacts of the existence of the Inland Fishery Business namely, the birth of a number of local entrepreneurs, an increase in the community economy and regional income. In the economic field, although not all of the welfare felt by business people is evenly distributed. Some business actors such as farmers, collectors and distributors are sufficient and have even reached the point of a successful economy. Of course the success points also have an impact on the region, both in terms of regional income and of course the good name of the area that has been dubbed the City of Bolu.